Stepper motor movement design based on FPGA - Freddy Artadima Silaban; Setiyo Budiyanto; Wahyu Kusuma Raharja (International Journal of Electrical and Computer Engineering (IJECE), 2020)
A stepper motor is an electro mechanical device that can convert electrical pulses to the axis of movement. The finding problem  in the movement of a stepper motor is  cannot respond to the clock signal directly because the motor windings require a clock (sequence) in the correct order. If the control signal given is not correct, the motor is not moving according to the specified precision. To answer these problems, it is necessary to move the stepper motor with a clock signal that works in real time. The research method is done by designing and testing the stepper motor movement in full stepp and half step with the direction of Clock Wise (CW) and Counter Clock Wise (CCW) movement. These are simulated by using FPGA Isim and implementation using a stepper motor. The results of several experiments have been carried out the stepper motor movement degree according to the input value entered,responding timely movement, and the direction of movement stepper motor.